Brassica oleracea L. Botrytis Group NGB 7740 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Brassica oleracea L. Botrytis Group Common name(s): BrassicaComplex, Cauliflower, Brassica complex Other names: Sami Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 7740 Method of creation: Acquisition Date: 1989-03-16 Historical: Yes Biological status: Advanced or improved cultivar MLS status: Included ...